MODIFICATION OF BEAN SPROUT AND UREA MEDIA TO SPIRULINA PLATENSIS CULTURE - Nadya Adharani; Selly Candra Citra; Nova Bagus Hidayat; Agung Hermawan Susanto; Angga Saputra (UPT Penerbitan Universitas Jember, 2016)
The development of microalgae culture Spirulina platensis is interesting until now, this was caused S. platensis has multi-function in several sector. High price of commercial media for the culture needs prompting to search alternative medium which is not expensive, such as sprouts extract (ET) and Urea. The Data of research from the experiment on commercial media and alternative using Standard Error of the Mean (SEM) are : The threatment K (Kontrol) with commercial media “walne”, the growth of S. Platensis cell is 22105 cell/ml and protein levels is 22.17%. Treatment P4 with alternative media (6% ET+120 ppm urea) showed that result of growth of S. Platensis cell is not too different to the threatment K, the result is 21136 cell/mL and protein level is 18.55%. Both experiment showed that the difference of growth cell between both experiment is not significant. Another result of treatment which used alternative media are: Treatment P2 (6% ET+100 ppm) growth cell is 16.383 cell/mL, protein level is 17.07%; Treatment P1 (4% ET+ 100ppm) growth cell is 10.7669 cell/mL, protein level 10.10%. The lowest of growth cell is treatment P3 (4% MT+120 ppm), growth cell is 10.769 cell/mL and protein level 13.81%. The conclusion is combination of ET and urea able to replace medium of microalga culture, it is like commercial medium